2012
DOI: 10.1080/17461391.2011.651490
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of home advantage in men's and women's football leagues in Europe

Abstract: Most research into home advantage is based on men's sports. This article analyses home advantage in the women's domestic football leagues of Europe and makes a comparison with the corresponding men's football leagues. A total of 47,042 games were included. From 2004 to 2010, home advantage existed in the domestic women's soccer leagues of all 26 European countries analysed, ranging from 51.0% to 58.8% and averaging 54.2%. In every country, this was less than the corresponding men's home advantage which average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
71
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 35 publications
3
71
1
6
Order By: Relevance
“…The data recorded in our study, although it did not show significant differences in the statistical analysis between the HPCs and IPCs, demonstrated that in the HPCs, motivated by the presence of a larger number of spectators in the stadiums and their influence on the environmental pressure on the visiting team's play and the decisions by the referees (Downward & Jones, 2007;Pollard, 2008;Page & Page, 2010;Pollard & Gómez, 2014), a more favourable context of play was observed for the home team over the visiting team, which showed a smaller percentage of victories in the HPCs in comparison with the IPCs (25.9% and 31.6%, respectively). Along this same line, a study developed by Armatas et al (2013), also highlighted that the advantage of playing at home was greater in the Greek Super Liga than in other Ligas Amateur in Greece.…”
Section: Study II Professionalization Of the Championshipmentioning
confidence: 92%
See 2 more Smart Citations
“…The data recorded in our study, although it did not show significant differences in the statistical analysis between the HPCs and IPCs, demonstrated that in the HPCs, motivated by the presence of a larger number of spectators in the stadiums and their influence on the environmental pressure on the visiting team's play and the decisions by the referees (Downward & Jones, 2007;Pollard, 2008;Page & Page, 2010;Pollard & Gómez, 2014), a more favourable context of play was observed for the home team over the visiting team, which showed a smaller percentage of victories in the HPCs in comparison with the IPCs (25.9% and 31.6%, respectively). Along this same line, a study developed by Armatas et al (2013), also highlighted that the advantage of playing at home was greater in the Greek Super Liga than in other Ligas Amateur in Greece.…”
Section: Study II Professionalization Of the Championshipmentioning
confidence: 92%
“…The results obtained in this section of Study I agree partially with those described by Gómez et al (2008), which confirm that in women's football matches, due to the fact that the level of tactical organization and defensive intensity of the teams is lower, the mean goals scored was higher than in men's football (1.85 and 1.15, respectively). Also, Pollard and Gómez (2014), in a study done on the 26 European leagues with the simultaneous presence of men's and women's Championships, they observed that the effect of home-field advantage was always more favourable in men's tournaments than in women's tournaments (p < 0.001). Another study done by the same authors (Pollard and Gómez, 2012), partially reconfirmed the results found in our study, concluding that the degree of variability in the final scores achieved by the teams (competitive balance) was lower in men's Championships than in women's Championships (1.76 and 2.33, respectively).…”
Section: Study I: Type Of Championshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The HA has been proved in cricket (Morley & Thomas, 2005), basketball (García, Saéz, Ibañez, Parejo & Cañadas, 2009), baseball (Levernier & Barrilla, 2007), volleyball (Marcelino, Mesquita, Palao & Sampaio, 2009;Marcelino, Mesquita & Sampaio, 2011), handball (Pollard & Gómez, 2012), water polo (Gómez, de la Serna, Lupo, & Sampaio, 2016), rugby (Gómez, Pollard & Luis-Pascual, 2011) and women's football (Pollard & Gómez, 2014). In relation to football, the HA has been studied and proved (Lago-Peñas & Lago-Ballesteros, 2011;Gómez, Gómez-López, Lago & Sampaio, 2012) in double elimination rounds (Page & Page, 2007), depending on the round (Pic & Castellano, 2016;Pic & Castellano, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Both approaches allowed reaching consistent conclusion about performance analysis of soccer and youth basketball players with a great impact of training drills. The gender effect has less studied in performance analysis research area (Pollard & Gómez, 2014). Accordingly, the special issue tried to incorporate some new analyses that accounted for females' performances.…”
mentioning
confidence: 99%